Mechanisms, interventions at risk and clinical presentation of iatrogenic nerve lesions in trauma patients - Aman, Martin; Zimmermann, Kim S.; Pennekamp, Anna; Thielen, Mirjam; Falkner, Florian; Eisa, Amr; Böcker, Arne Hendrik; Harhaus-Wähner, Leila (Archives of orthopaedic and trauma surgery, 2023)
Iatrogenic nerve lesions during surgical interventions are avoidable complications that may cause severe functional impairment. Hereby, awareness of physicians and knowledge of structures and interventions at risk is of utmost importance for prevention. As current literature is scarce, we evaluated all patients treated surgically due to peripheral nerve injuries in our specialized nerve center for the presence of iatrogenic nerve lesions.